Integration of Industry 4.0 and Lean Six Sigma: Critical Success Factors for Overcoming Socioeconomic Challenges in the Telecommunication Sector - Ahmed Said El Shenawy; Nevien F. Khourshed; Mohamed A. Ragheb; Mahmoud H. Beshr (SocioEconomic Challenges)

(untitled)
The telecommunications industry faces significant socioeconomic challenges that impede competitiveness and operational excellence. Industry 4.0 and Lean Six Sigma offer solutions to these challenges through process automation, data-driven decision-making, and continuous improvement. From October 2023 to October 2024, semi-structured interviews with open-ended questions were conducted with 12 employees from Egyptian telecommunications companies. Respondents, each with 10 to 20 years of experience, were drawn from quality departments (4), business processes (4), and information technology (4). The Analytical Hierarchy Process was used to identify and prioritize critical success factors. The interviews were about four things: the respondents' experience and thoughts on putting Lean Six Sigma into practice in telecommunications; comparing five key success factors for Industry 4.0 and seven key success factors for Lean Six Sigma; and having a free-flowing conversation about problems that came up and what was learned from them. I'm currently working on Operations Management System projects. The study identified strong management commitment (51.0%) as the most significant factor. Critical factor for Industry 4.0 and Lean Six Sigma integration, followed by training programs (24.5%) and new information technologies (12.8%). For Lean Six Sigma alone, top management commitment was ranked highest (39.7%), with training programs (30.1%) and understanding Lean Six Sigma tools (13.1%) following. These findings provide a framework for integrating Industry 4.0 and Lean Six Sigma in telecommunications. These ideas help organizations in developing countries like Egypt develop dynamic management plans that align with operational excellence and continuous improvement. It will make processes run more smoothly and make better use of resources.